1973
DOI: 10.1111/j.2042-7158.1973.tb09131.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of diferuloyl methane (curcumin), a non-steroidal anti-inflammatory agent

Abstract: Some pharmacological actions of curcumin (diferuloyl methane) have been examined in rats, mice and cats. The compound possesses significant anti-inflammatory activity in acute as well as in chronic models of inflammation. It is as potent as phenylbutazone in the carrageenan oedema test but only half as potent in chronic tests. Curcumin possesses a much lower ulcerogenic index than phenylbutazone. It prevents the inflammation induced increase in SGOT and SGPT levels. It lacks analgesic and antipyretic activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
310
0
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(322 citation statements)
references
References 10 publications
6
310
0
6
Order By: Relevance
“…Pharmacological actions of curcumin as an antiinflammatory agent have been examined by Srimal and Dhawan (1973). In this work, the authors reported that the compound was effective in acute as well as chronic models of inflammation.…”
Section: Chemistrymentioning
confidence: 84%
“…Pharmacological actions of curcumin as an antiinflammatory agent have been examined by Srimal and Dhawan (1973). In this work, the authors reported that the compound was effective in acute as well as chronic models of inflammation.…”
Section: Chemistrymentioning
confidence: 84%
“…and cholagogic (Ramprasad and Sirrsi, 1957), antibacterial (Lutomsky et al, 1974;Shankar and Murthy, 1979), antihepatotoxic (Claeson et al, 1994), antiinflammation (Srimal and Dhawan, 1973;Claeson et al, 1994), antioxidant (Sharma et al, 1972), anticancer (Kuttan et al, 1985), and antivirus (Mazumder et al, 1997). Modification of curcumin molecule into some molecules to improve the pharmacological effects have been done in saveral research groups.…”
Section: Introductionmentioning
confidence: 99%
“…10 Pharmacologically, curcuminoids have been reported to possess significant anti-inflammatory properties. 11 In vitro studies have shown that curcuminoids exert anti-apoptotic actions on interleukin (IL)-1b-stimulated human articular chondrocytes. 12,13 Laboratory models have demonstrated that curcuminoids inhibit pro-inflammatory mediators, including prostaglandin (PG)E2, nitric oxide, IL-6 and IL-8 in bovine chondrocytes.…”
Section: Introductionmentioning
confidence: 99%